Theory of error and least square adjustment: Application in coordinate transformation - Adhikari, Madhusudan (Journal on Geoinformatics, Nepal, 2009)
After detection and elimination of blunders, determination and correction of systematic errors the remaining random errors are adjusted by the method of least square. It is very useful technique in survey adjustments; as an example of its application, adjustment of conformal transformation of coordinate has been presented in this paper.